1999
DOI: 10.1111/j.1539-6924.1999.tb00436.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Consumers' Risk Perceptions Toward Recombinant Bovine Growth Hormone (rbGH): The Impact of Risk Characteristics

Abstract: This study estimates the effect risk characteristics, described as outrage factors by Hadden, have on consumers' risk perceptions toward the food-related biotechnology, recombinant bovine growth hormone (rbGH). The outrage factors applicable to milk from rbGH treated herds are involuntary risk exposure, unfamiliarity with the product's production process, unnatural product characteristics, lack of trust in regulator's ability to protect consumers in the marketplace, and consumers' inability to distinguish milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 19 publications
(2 reference statements)
3
43
0
Order By: Relevance
“…This may explain why in our study the older subjects expressed the view that the Government had more responsibility to protect them from risks associated with Salmonella, whereas the younger subjects felt that it was more their own responsibility. Risk perceptions have been shown to increase with age to a point and then to decrease with age, possibly due to other health concerns of ageing (Grobe et al, 1999). In fact, Salmonella is more common in children and young adults than in the elderly (Forsythe, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may explain why in our study the older subjects expressed the view that the Government had more responsibility to protect them from risks associated with Salmonella, whereas the younger subjects felt that it was more their own responsibility. Risk perceptions have been shown to increase with age to a point and then to decrease with age, possibly due to other health concerns of ageing (Grobe et al, 1999). In fact, Salmonella is more common in children and young adults than in the elderly (Forsythe, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, more women responded to the questionnaire than men. There is a well established difference in risk perception between men and women, with women tending to perceive more risk from a hazard than men (Grobe et al, 1999;Frewer, 2000). Even so, risk communication messages need to take these differences into account, especially since, in general, women tend to have responsibility for food purchasing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trust has also been found to be strongly linked to risk perceptions. For instance, Grobe et al (1999) found that greater trust in the US Food and Drug Administration as a food-related information source was related to less concern about the adverse health effects from the use of recombinant bovine growth hormone. These findings suggest a direct relationship between distrust in regulatory agencies and risk perceptions.…”
Section: Trustmentioning
confidence: 99%
“…3,7,10 Early risk communication research centered on debates about the health or environmental risks associated with waste disposal, toxic chemicals and heavy metals, air and water pollution, nuclear power, electric and magnetic fields, oil spills, food additives, radon in homes, and biotechnology. 2,[11][12][13][14][15][16][17] Little attention was paid to risks caused by exposure to pathogens or to health belief models developed for addressing personal risk-taking behavior (e.g., smoking, alcohol consumption, and drug addiction).…”
mentioning
confidence: 99%